Rattus norvegicus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
659. Brown Rat Rattus norvegicus French: Rat brun / German: \Wanderratte / Spanish: Rata parda Other common names: Common Rat, Domestic Rat, Fancy Rat, Lab Rat, Norway Rat, Sewer Rat Taxonomy. Mus norvegicus Berkenhout, 1769, “Great Britain.” Rattus norvegicus is currently in the R. nor- vegicus species group, along with R. nitidus and R. pyctoris, based on genetic and morphological data. There is less genetic and morphological variation in R.norvegicus than R. rattus, which was recently broken up into multiple species. Rattus norvegicus originated in south-western Siberia, northern China, and Japan and spread throughout Asia and Europe as early as the 16" century, although this is unconfirmed and the actual date when it became commensal with humansis uncertain. Since Western Civilization began colonizing the New World and Australia, R. norvegicus followed, spreading in similar ways as R. rattus, stowing away on ships. Subfossils of Brown Rats can be found all over the world and are indicators of when and where some occurred or became extinct. Genetic studies are needed to identify possible subspecies and to determine the way in which it spread across the world. Subspecific taxonomy requires further investigation. Distribution. Originally native to N China (possibly Mongolia), SW Siberia in Russia, and Japan, and now introduced worldwide, except Antarctica (modern introductions not shaded on the map). Descriptive notes. Global: head-body 160-290 mm, tail 122-250 mm, ear 15-26 mm, hindfoot 30-50 mm; weight 195-540 g (known to reach 1 kg in rare cases in cities with lots of available resources). China: head—body 205-260 mm, tail 190-250 mm, ear 19-26 mm, hindfoot 38-50 mm; weight 230-500 g. Russia: head—body 140-248 mm,tail 100-220 mm, ear 17-22 mm, hindfoot, 27-44 mm. South-east Asia: head-body 160-265 mm,tail 170-250 mm, hindfoot 35-50 mm; weight 200-500 g. Australia: head—body 180-255 mm,tail 150-210 mm, ear 16-20 mm, hindfoot 35-45 mm; weight 280-500 g. Europe: head-body 190-290 mm,tail 170-230 mm, ear 19-22 ...